Supervision : a Foucaultian exploration of institutional and interpersonal power relations between postgraduate supervisors, their students and the university domain - Rau, Asta (Rhodes University, Faculty of Education, Department of Education, 2005)
Supervision is widely acknowledged as influencing the quality of postgraduate theses, and by association, of postgraduates. Despite this, publications on conducting research offer far less guidance on managing the supervision relationship than on the practicalities of producing a thesis. In-depth, qualitative supervision studies are few and fewer still examine power in the supervision relationship. Michel Foucault's insights are used to explore the question: How do postgraduate supervisors and their Master's students experience the supervision relationship and how are the dynamics of interpersonal and institutional power implicated in these relationships? Foucault argues that power relations always involve resistances; these function primarily through institutionalized discourses to produce different forms of knowledge, one form of which is identity or subjectivity. Accordingly, power relations are explored in terms of thesis-as-product, person-as-product and the impact of both on the mediation of knowledge in the educational domain. Four institutionalized discourses in the university domain are examined: · Commercial educational management discourse: targets academics through issues of quality assurance, throughput, publication, research productivity and funding. · Anarchic educational leadership discourse: integrates quantum principles with commercial demands, change management strategies and meaningful participation. · Humanistic discourse: favours a pastoral ethic and is person-centered. · Holistic discourse: cultivates ecological sensibility and values the interconnectedness of all aspects of being-in-the-world. Data collected in sixteen semi-structured interviews with three matched supervisor-student pairs selected from the humanities and education faculties of one South African university, are presented as case studies. Data analysis combines grounded theory techniques with selected aspects of Foucault's methods. A conceptual model is devised to analyse how participants use resistance strategies to interface their autonomy and dependency with their expectations, abilities, and professional and pastoral care. The research yields rich data in which several thematic correlations in interpersonal and institutional power dynamics are grounded. These include: the significance of supervisor-student matching; links between expectations, abilities, the way participants negotiate power and the quality of professional and pastoral care they experience; the benefit of personal affinity to thesis-as-product and person-as-product; and the impact of commercial demands on participants' power relations. Participants tend to reproduce the discourses in which they are embedded and adopt or adapt aspects of contesting discourses to this end. Potential avenues are identified for improving supervision practice and for further research.
Keywords: Foucault, Michel, 1926-1984 -- Methodology; Foucault, Michel, 1926-1984 -- Criticism and interpretation; Graduate students -- Supervision of; Dissertations, Academic